Compact Ionized Gas Region Surrounded by Porous Neutral Gas in a Dusty Lyman Break Galaxy at Redshift z = 8.312 - Masato Hagimoto; Yoichi Tamura; Akio K. Inoue; Hideki Umehata; Tom J. L. C. Bakx; Takuya Hashimoto; Ken Mawatari; Yuma Sugahara; Yoshinobu Fudamoto; Yuichi Harikane; Hiroshi Matsuo; Akio Taniguchi (The Astrophysical Journal)
Porous interstellar medium (ISM) structure in galaxies at the epoch of reionization gives us a hint to understand what types of galaxies contribute to reionization. Although recent studies have pointed out the positive correlation between high ionizing photon escape fractions and high [O iii ] 88 μ m/[C ii ] 158 μ m ratios found in UV-luminous star-forming galaxies at z > 6 with the Atacama Large Millimeter/submillimeter Array, previous studies have paid little attention to the neutral gas porosity that allows ionizing photons to escape. Here we present a detailed analysis of a z = 8.312 Lyman break galaxy, MACS0416_Y1 with a high L _[O _III _] 88 _μ _m / L _[C _II _] 158 _μ _m ratio (≈9) and dust continuum detection. We construct a multiphase ISM model incorporating the neutral gas covering fraction ( c ov _PDR ). The best-fit model reveals a cov _PDR ≈ 25%, indicating that ≈75% of the ionized gas region is exposed to intercloud space. We confirm that our conclusions hold even when varying star formation history, stellar age, gas/stellar metallicity, and carbon-to-oxygen abundance ratio. This finding meets one of the necessary conditions for galaxies to have a nonzero escape fraction of ionizing photons and supports recent studies that galaxies with a high [O iii ] 88 μ m/[C ii ] 158 μ m ratio, such as MACS0416_Y1, could contribute to cosmic reionization. Furthermore, the modeled H ii region with the best-fitting parameters has a typical size ( D = 0.90 pc) and gas density ( ${log}\,{n}_{{\rm{H}},{\rm{c}}}/{{\rm{cm}}}^{-3}=2.7$ ) that are comparable to local compact H ii regions. This suggests that the H ii regions in MACS0416_Y1 are in an early evolutionary stage.